Environment and Development Economics (Cambridge)
This Journal is divided into two main sections, Theory and Applications, which includes regular academic papers and Policy Options, which includes papers that may be of interest to the wider policy community. Environment and Development Economics also publishes occasional Policy Fora (discussions based on a focal paper). Recent special issues have included ?China?s Environmental Policy.
Keywords: Economics